2020
DOI: 10.5194/acp-20-8003-2020
|View full text |Cite
|
Sign up to set email alerts
|

Smoke of extreme Australian bushfires observed in the stratosphere over Punta Arenas, Chile, in January 2020: optical thickness, lidar ratios, and depolarization ratios at 355 and 532 nm

Abstract: Abstract. We present particle optical properties of stratospheric smoke layers observed with multiwavelength polarization Raman lidar over Punta Arenas (53.2∘ S, 70.9∘ W), Chile, at the southernmost tip of South America in January 2020. The smoke originated from the record-breaking bushfires in Australia. The stratospheric aerosol optical thickness reached values up to 0.85 at 532 nm in mid-January 2020. The main goal of this rapid communication letter is to provide first stratospheric measurements of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(123 citation statements)
references
References 58 publications
7
92
0
Order By: Relevance
“…The 2019-2020 fire season in Australia resulted in 18.6 million burned hectares, most of them in the New South Wales and Victoria southeastern states (SBS News, 2020). It is estimated that tens of people died along with billions of animals that were exterminated, including species that were near extinction before the fire (Readfearn, 2020). The intense fire activity likely triggered a number of pyroCb clouds over a few days between 30 December 2019 and early January 2020, injecting large quantities of carbonaceous aerosols into the Southern Hemisphere UTLS (Ohneiser et al, 2020).…”
Section: Australia 2019-2020 Firesmentioning
confidence: 99%
“…The 2019-2020 fire season in Australia resulted in 18.6 million burned hectares, most of them in the New South Wales and Victoria southeastern states (SBS News, 2020). It is estimated that tens of people died along with billions of animals that were exterminated, including species that were near extinction before the fire (Readfearn, 2020). The intense fire activity likely triggered a number of pyroCb clouds over a few days between 30 December 2019 and early January 2020, injecting large quantities of carbonaceous aerosols into the Southern Hemisphere UTLS (Ohneiser et al, 2020).…”
Section: Australia 2019-2020 Firesmentioning
confidence: 99%
“…In fact, the smoke load in the stratosphere was found to be comparable to that of a moderate volcanic eruption (Peterson et al, 2018). The smoke plumes encircled the Northern Hemisphere in nearly 20 d, reaching Europe in less than 10 d. Above Europe, their properties were intensively studied by the European Aerosol Research Lidar Network (EARLINET; Pappalardo et al, 2014). Multi-wavelength lidar measurements in central (Ansmann et al, 2018;Haarig et al, 2018;Hu et al, 2019) and southern Europe (Sicard et al, 2019) revealed high PLDR values at 355 and 532 nm and a strong spectral dependence from the UV to the near-IR wavelength.…”
mentioning
confidence: 99%
“…It is easy to generate overestimates of rising rates from a structure moving over a fixed observatory. For instance, Ohneiser et al (2020), and yourself in your comment claim an ascent rate of 1km/day when Koobor was near the tip of South America which is about three time the ascent rate found by Khaykin et al (2020) (corroborated by Allen et al (2020)) at the same time on the trajectory. The ascent of Koobor was basically smooth for three months, es-pecially in potential temperature, except during two episodes of vertical split and it rose from about 16 km to 35 km, which is a considerable way against the Brewer-Dobson circulation but it did not reach the ionosphere.…”
mentioning
confidence: 64%